Case Report: Two cases of adrenal hemangioma and literature analysis - Dong, Xiaochen; Wang, Min (Frontiers in Oncology, 2025)
Adrenal hemangioma is a rare benign tumor that is often misdiagnosed due to its low incidence and limited clinical awareness. We report two cases of adrenal hemangioma and provide a detailed description of their CT and MRI imaging features, surgical findings, and pathological characteristics. Both patients were elderly males, and the adrenal hemangiomas were incidentally discovered during imaging examinations. The lesions were unilateral, with one case on the left side and the other on the right side. The sizes were approximately 3.4 cm × 3.6 cm × 3.5 cm and 6.7 cm × 9.0 cm × 8.8 cm, respectively. The margins were well-defined, and both lesions were quasi-circular. On Fat-suppressed T2-weighted (T2WI-FS), the lesion showed heterogeneous hyperintensity, while on Diffusion-weighted imaging (DWI), the lesion demonstrated no restricted diffusion. On contrast-enhanced CT and MR imaging, the lesion shows peripheral nodular enhancement with delayed centripetal filling. Additionally, a well-defined, rim-enhancing tumor capsule is observed. Our case report aims to increase awareness of this rare adrenal tumor.